High methoxyl pectin–methyl cellulose films with antioxidant activity at a functional food interface - Perez, C. D. (2012)
The effect of using increasing proportions of methylcellulose (MC) for the development of glycerol plasticized films based on high methoxyl pectin (HMP) (30:70, 50:50 and 70:30 w/w HMP:MC) and carrying L-(+)-ascorbic acid (AA) was studied with the purpose of achieving higher stability of AA and localized antioxidant activity at food interfaces. MC and 30:70 HMP:MC systems could not be casted. The shelf-life of the other AA-active films was assessed by storage at 25 C, constant relative humidity (RH: 33.3%, 57.7% and 75.2%) and vacuum conditions. The rate constant for AA hydrolysis increased with the RH and, hence, with water mobility. Browning and AA degradation rates were directly related. When stored at 75.2% RH, both decreased as MC proportion increased. Compared to HMP film, the highest proportion of MC (50:50 HMP:MC) showed the highest AA stabilization under vacuum and greater performance under air atmosphere. They also developed localized antioxidant activity preserving the tocopherol content of walnut oil.